2020
DOI: 10.21037/jtd-20-2400
|View full text |Cite
|
Sign up to set email alerts
|

Time to surgery in thoracic cancers and prioritization during COVID-19: a systematic review

Abstract: Background: Coronavirus disease 2019 (COVID-19) has overwhelmed hospital resources worldwide, requiring widespread cancellation of non-emergency operations, including lung and esophageal cancer operations. In the United States, while hospitals begin to increase surgical volume and tackle the backlog of cases, the specter of a "second wave," with a potential vaccine months to years away, highlights the ongoing need to triage cases based upon the risk of surgical delay. We synthesize the available literature on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 46 publications
0
26
0
1
Order By: Relevance
“…Studies in Western countries have highlighted the omission of some pretreatment examinations and treatment changes during the COVID-19 pandemic ( 4 , 17 ). Moreover, prolonged surgery waiting time due to the COVID-19 pandemic has been suggested to decrease postoperative survival ( 23 ). Therefore, radiation therapy, which is less susceptible to the effects of COVID-19, is expected to complement surgical treatment ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Western countries have highlighted the omission of some pretreatment examinations and treatment changes during the COVID-19 pandemic ( 4 , 17 ). Moreover, prolonged surgery waiting time due to the COVID-19 pandemic has been suggested to decrease postoperative survival ( 23 ). Therefore, radiation therapy, which is less susceptible to the effects of COVID-19, is expected to complement surgical treatment ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that breast cancer has the ability to achieve pathological complete response on systemic therapy and often has a measurably better prognosis with the use of neoadjuvant therapy 10,14 . However, lung and esophageal cancers, although also good responders to neoadjuvant therapy, have a lower survival rate with surgical delay 15 . The increased use of neoadjuvant therapy was not dependent on the type of practice.…”
Section: Discussionmentioning
confidence: 99%
“…for 81.7 % benign and 37.7 % malignant lesions) to be cancelled or postponed worldwide during the first 12 weeks of the pandemic peak in 2020 [16]. Multiple studies showed the medical impact of postponed mandatory diagnostic and surgical procedures [17,18].…”
Section: Discussionmentioning
confidence: 99%